Determinantes dos custos do crédito bancário e desenvolvimento do mercado de crédito no Brasil de 2000 a 2013 - Garzillo, Daniel Barbosa (2014)
Despite being an important variable for development of economies, by financing expenditure and investment projects, the credit market is few developed in Brazil when compared to the most developed countries. This fact seems to be strongly correlated with high spreads and interest rate on bank loans charged by the Brazilian banking sector. The orthodox theory is the one that most deeply study this topic and point to five main reasons as determinants of different credit costs between countries: competition in the banking sector; macroeconomic environment; taxation, reserves requirement and mandated lending; and availability of information about borrowers. Assessing Brazil in the indicated items, there is notable improvement in almost all factors during de 2000s, however, despite of the cutbacks in interest rates and spreads, we can explain only partially the reduction observed and, in addiction, we note that the credit costs in Brazil are still high comparing to other countries. We understand that SELIC may explain the high level of Brazilian credit costs, because beyond affect directly the costs of funding, it represents a high cost of opportunity of offering credit, since SELIC remunerate part of Brazilian treasury bills, which become profitable, low risk and high liquidity assets